INFLUENCE OF INCOME FOR MUDHARABAH AND MUSYARAKAH RESULTS ON PROFITABILITY LEVEL OF SHARIA COMMERCIAL BANKS 2015-2019 - Agriani, Tia Nenes; Pardistya, Irvan Yoga (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This study aims to determine, explain and analyze the influence of mudharabah and Masyarakat profit-sharing revenue on profitability (ROA). The object of this research is Islamic banks in Indonesia in 2015-2019, mudharabah, musharaka, and profitability registered in the Financial Services Authority (OJK) in 2015-2019. The sample used was 4 banks from 14 listed Islamic commercial banks using the purposive sampling method, the data analysis method used was a descriptive analysis test, a classic assumption test, multiple linear regression analysis, and a hypothesis. The following conclusions are obtained: (1) Mudharabah partially has a significant positive effect on the profitability (ROA) of Islamic commercial banks (2) Musyarakah has a negative and significant effect simultaneously on profitability (ROA) of Islamic commercial banks.